The Impact of Digital Marketing Technology Development on the Growth of Pekalongan Batik MSMEs via Social Media and Marketplaces - Jamil, Muhammad; Adinugraha, Hendri Hermawan (Institute Of Advanced Knowledge and Science, 2024)
There have been changes in many facets of human life due to technology’s ever-accelerating development. All human affairs and everyday tasks can now be made simpler thanks to technological advancements; the marketing and product sales industry is just one example. These days, technology can help to simplify marketing; it can even be used to sell goods directly to customers online. Naturally, the advancement of this technology benefits both buyers and sellers, as it facilitates the purchasing and exploration of products via digital networks. The growth of MSMEs (micro, small, and medium-sized enterprises), particularly Batik, is greatly influenced by the advancement of digital marketing. Digital marketing facilitates the marketing of batik products by allowing producers or sellers to directly market their products in real-time via social media or marketplaces. The purpose of this study was to examine how advancements in digital marketing technology have affected MSMEs, particularly Batik in Pekalongan. Information is gathered through field observations and observations. It is hoped that the research's findings will shed light on the advancements faced by Batik MSMEs that have adopted digital marketing or digital network marketing, as well as explain the advantages of digital marketing for company growth.